STATISTICAL ANALYSIS OF THE 2004 UKRAINIAN PRESIDENTIAL ELECTION FIRST-ROUND RESULTS FOR POLLING STATIONS IN LUHANSK REGION - Крикун, Іван (SWorldJournal, 2025)
This study examines the results of the first round of the 2004 Presidential Elections of Ukraine at the polling stations in the Luhansk region. A statistical analysis of the published results was conducted using the indicators of voter turnout and the nu